Psychological wellbeing in a resource-limited work environment: examining levels and determinants among health workers in rural Malawi - Lohmann, Julia; Shulenbayev, Olzhas; Wilhelm, Danielle J.; Muula, Adamson S.; De Allegri, Manuela (Human resources for health, 2019)
A competent, responsive, and productive health workforce is central to a well-performing health system capable of providing universal access to high-quality care. Ensuring health workers’ psychological wellbeing is critical to sustaining their availability and productivity. This is particularly true in heavily constrained health systems in low- and lower-middle-income countries. Research on the issue, however, is scarce. This study aimed to contribute to filling the gap in knowledge by investigating levels of and factors associated with psychological wellbeing of mid-level health workers in Malawi.
Gesehen am 22.01.2020